2021
DOI: 10.1016/s2215-0366(21)00235-2
|View full text |Cite|
|
Sign up to set email alerts
|

Therapist-supported online remote behavioural intervention for tics in children and adolescents in England (ORBIT): a multicentre, parallel group, single-blind, randomised controlled trial

Abstract: Background Exposure and Response Prevention (ERP) is a form of behavioural therapy for tics; however, its effectiveness remains uncertain. We aimed to evaluate the effectiveness of internet-delivered, therapist-supported, and parent-assisted ERP for treatment of tics in children and young people with Tourette syndrome or chronic tic disorder.Methods This multicentre, parallel group, single-blind, randomised controlled trial was conducted across two study sites in England. Participants were recruited via 16 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
60
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 49 publications
(65 citation statements)
references
References 30 publications
2
60
3
Order By: Relevance
“…The results showed that ICBIT had a comparable effect on tic reduction in participants with ADHD. These data are consistent with studies indicating that children and teens with ADHD can benefit comparably from CBIT as was found in previous studies [ 10 , 21 ]. However, the current study showed that although both tics and functional impairment of the participants with co-occurring ADHD improved, they had lower CGAS scores, indicating greater impairment, compared to the participants without ADHD.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The results showed that ICBIT had a comparable effect on tic reduction in participants with ADHD. These data are consistent with studies indicating that children and teens with ADHD can benefit comparably from CBIT as was found in previous studies [ 10 , 21 ]. However, the current study showed that although both tics and functional impairment of the participants with co-occurring ADHD improved, they had lower CGAS scores, indicating greater impairment, compared to the participants without ADHD.…”
Section: Discussionsupporting
confidence: 93%
“…However, other studies have reported that children and adolescents with TD and ADHD were able to suppress tics, and that tic suppressibility did not differ as a function of the presence or absence of ADHD comorbidity [ 19 , 20 ]. Yet, other studies have indicated that ADHD did not impede the effects of behavioral treatment [ 10 , 21 ]. Hence, further research is needed to clarify whether comorbid ADHD influences the response outcomes of behavioral treatment in children and teens.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to our results at 3 months after end of treatment, they observed a nearly identical estimated mean difference in tic reduction between ERP and placebo (−2.29 [−3.86; 0.71] vs. −2.25 [−3.75; −0.75]). Despite several differences between the study of Hollis et al [ 37 ] and our study (e.g., length of treatment period, participants’ age), the nearly identical tic reduction after iCBIT and ERP, respectively, further supports the hypothesis that both behavioral interventions, HRT/CBIT and ERP, are comparably effective [ 38 ].…”
Section: Discussionsupporting
confidence: 79%
“…Interestingly, only recently, Hollis et al [ 37 ] reported the results of a randomized controlled study investigating a therapist-supported online remote exposure and response prevention training (ERP) in n = 224 children and adolescents with CTD/TS and examined effects on tics compared to psychoeducation after a 3 month treatment period using the YGTSS-TTS. Compared to our results at 3 months after end of treatment, they observed a nearly identical estimated mean difference in tic reduction between ERP and placebo (−2.29 [−3.86; 0.71] vs. −2.25 [−3.75; −0.75]).…”
Section: Discussionmentioning
confidence: 99%